2020
DOI: 10.1177/0163443720926040
|View full text |Cite
|
Sign up to set email alerts
|

Television and Black Twitter in South Africa: Our Perfect Wedding

Abstract: This article examines Twitter use by audiences of the popular South African television show, Our Perfect Wedding. We argue that the show’s Twitter feed provides an extension of South Africa’s ‘Black Twitter’ facilitating a space for recognition and group identity for Black South African television viewers. Such a space is significant since Black audiences have been neglected in the short history of South African television broadcasting. On Our Perfect Wedding, broadcast on a satellite television service DStv t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Public opinion on social media offers an avenue to examine contestations between different perspectives. 1 Studies on multiple contexts-such as Norway, 2 Russia, 3 South Africa, 4 Colombia, 5 Finland, 6 India, 7 the United States, 8 Syria, 9 Spain, 10 the United Kingdom, 11 Ukraine, 12 Japan, 13 and Australia 14 -have shown that public opinion on Twitter serves as a lens through which seemingly disconnected social and contextual factors are organized as related parts of a whole. In the Nigerian context, while some researchers have investigated perceptions of corruption and cybercrime, 15,16,17,18,19 none used Twitter as a data source.…”
Section: Public Opinion On Twittermentioning
confidence: 99%
“…Public opinion on social media offers an avenue to examine contestations between different perspectives. 1 Studies on multiple contexts-such as Norway, 2 Russia, 3 South Africa, 4 Colombia, 5 Finland, 6 India, 7 the United States, 8 Syria, 9 Spain, 10 the United Kingdom, 11 Ukraine, 12 Japan, 13 and Australia 14 -have shown that public opinion on Twitter serves as a lens through which seemingly disconnected social and contextual factors are organized as related parts of a whole. In the Nigerian context, while some researchers have investigated perceptions of corruption and cybercrime, 15,16,17,18,19 none used Twitter as a data source.…”
Section: Public Opinion On Twittermentioning
confidence: 99%
“…As a television producer for the Norwegian version of Pop Idol argues: 'The whole format is made to be interactive TV, meaning it has a presence on all available platforms' (ibid: 468). Other more recent examples of programmes that have used social media to 'eventize' their output include Scandal in the USA (Everett, 2015), X Factor NZ in New Zealand (Stewart, 2020) and Our Perfect Wedding in South Africa (Smit & Bosch, 2020).…”
Section: Pseudo Eventsmentioning
confidence: 99%
“…This is especially true for reality dating shows, which have managed to form strong virtual communities such as the “ Bachelor nation.” Although the different types of engagement of these virtual communities through the use of a Twitter # are becoming a popular area of study, this paper moves beyond the engagement inventory itself and looks at the culture inherent in the engagement (Sheldon et al 2020). To do this, I borrow from a South African virtual community around a popular dating show Date My Family because, amongst the more popular RTV formats, dating shows have proven to be the favorite choice in South Africa (Smit and Bosch 2020).…”
Section: Introductionmentioning
confidence: 99%